Correlation of CTR1, ERCC-1, and HSP70 expressions with cisplastin response in cervical cancer stage IIB - Brahmana Askandar; Suhatno Suhatno; Juliati Hood (Majalah Obstetri dan Ginekologi, 2019)
Objectives: This study aimed to determine the resistance of cisplatin (chemotherapy drugs) at three point areas including expression of CTR1, ERCC1, and HSP70 in cervical cancer patients.Materials and Methods: This research used a cross sectional approach. The population in this study were patients with stage IIB of cervical carcinoma. The study sample were patients with stage IIB of cervical carcinoma according to the FIGO classification, patients received cisplatin chemotherapy treatment (50 mg/m2 4 times), had good kidney and liver function. The independent variables in this study were the expression of CTR1, ERCC1, and HSP70 and the dependent variable of this study was the response to cisplatin therapy in cervical cancer. Primary data was obtained through MRI examination after the administration of cisplatin 50 mg/m2 every week. The parameters of this study included the expression of CTR1, ERCC1 and HSP70. Data obtained were analyzed using Wilcoxon rank test, Spearman test and categorical regression with a significance level of p <0.05.Results: The treatment of cisplatin therapy in cervical cancer patients had no significant correlation between the expression of CTR1 and ERCC1, but in the expression of HSP70 there was a significant negative correlation which means that the higher the expression of HSP70, the worse the response of therapy.Conclusion: This study showed that HSP70 expression can be used as an indicator in treatment of cisplatin therapy in cancer patients through MRI examination.